信越地域の鮮新統および下部更新統産Astartidae(二枚貝) - 天野, 和孝; アマノ, カズタカ; Amano, Kazutaka (上越教育大学, 1994)
信越地域の鮮新統および下部更新統から産出するAstartidae（二枚貝）の分類について総括し，信越地域のAstartidae中にAstarte hakodatensis Yokoyama，A．sp.，Tridonta alaskensis（Dall），T. borealis Schumacherの4種を認めた。このうち，Astarte sp．は殻高が低く，殻頂が前方に寄り，成長肋が明瞭なことでA．hakodatensisとは区分されること，これまでに報告のない種であることが明らかになった。Tridonta属の方がAstarte属に比べて早期に出現し，Tridonta alaskensisが従来考えられていたよりも早く，4～5Maに出現したことも明らかになった。これはカムチャッカ東方のカラギンスキー島の貝化石群などから推定されているベーリング陸橋崩壊時期とほぼ一致している。 Many specimens of Astartidae were obtained from the Pliocene and Lower Pleistocene deposits in the Shin'etsu district (Nagano and Niigata Prefectures), Central Japan. These are identified with the following four species; Astarte hakodatensis Yokoyama, A. sp., Tridonta alaskensis (Dall) and T. borealis Schumacher. Among them, Astarte sp. was newly found from the Early Pleistocene Haizume Formation and was hitherto undescribed. This species differs from Astarte hakodatensis by having elongate ovate shells, anteriorly situated beak and distinct concentric ribs. It is allied to Asatrte crenata (Gray) living in Arctic and Atlantic regions. In the Shin'etsu district, the genus Tridonta appeared earlier than the Astarte. Especially, Tridonta alaskensis was collected from the Tomikura and Arakurayama Formations which had been dated as 4-5Ma by K/Ar dating method. This period nearly coincides with that of first appearance of Tridonta in Karaginsky Island which occurred by the opening of Bering Strait. departmental bulletin paper